Identification of a SARS-like bat coronavirus that shares structural features with the spike glycoprotein receptor-binding domain of SARS-CoV-2. Issue 11 (8th November 2020) - Fraguas Bringas, Conchita; Booth, David
Abstract : SARS-CoV-2 is a recently emerged coronavirus that binds angiotensin-converting enzyme 2 (ACE2) for cell entry via its receptor-binding domain (RBD) on a surface-expressed spike glycoprotein. Studies show that despite its similarities to severe acute respiratory syndrome (SARS) coronavirus, there are critical differences in key RBD residues when compared to SARS-CoV-2. Here we present a short in silico study, showing that SARS-like bat coronavirus Rs3367 shares a high conservation with SARS-CoV-2 in important RBD residues for ACE2 binding: SARS-CoV-2's Phe486, Thr500, Asn501 and Tyr505; implicated in receptor-binding strength and host-range determination. These features were not shared with other studied bat coronaviruses belonging to the betacoronavirus genus, including RaTG13, the closest reported bat coronavirus to SARS-CoV-2's spike protein. Sequence and phylogeny analyses were followed by the computation of a reliable model of the RBD of SARS-like bat coronavirus Rs3367, which allowed structural insight of the conserved residues. Superimposition of this model on the SARS-CoV-2 ACE2-RBD complex revealed critical ACE2 contacts are also maintained. In addition, residue Asn488Rs3367 interacted with a previously defined pocket on ACE2 composed of Tyr41, Lys353 and Asp355. When compared to available SARS-CoV-2 crystal structure data, Asn501SARS-CoV-2 showed a different interaction with the ACE2 pocket. Taken together, this study offers molecular insights on RBD-receptor interactions with implications for vaccine design.